An Analysis of Euphemism in The Captions of Folkative Instagram Accounts - Wibowo, Hanafi; Ramadhani, Nurul Luthfia (Tamaddun Life, 2024)
This research discusses about “An Analysis of Euphemism in the captions of Folkative Instagram accounts”. The purpose of this research is focused on two things, namely: Identifying the types and functions of euphemisms found in captions of Folkative Instagram account. This research used descriptive qualitative method. Data collection techniques involved reading the captions posted by Folkative on January-March 2023 and note-taking captions that contain euphemisms, and the last classify data selection based on type and function of euphemism. Data on the types of euphemisms were analyzed based on the theory of Allan and Burridge, and the function of euphemisms was analyzed using the theory of Rusman. In addition, the data source is the Captions of Folkative Instagram account from January-March 2023. The research focused on @Folkative Instagram account. The results of this research found 129 data. The researcher found 10 types of euphemisms used in captions for Instagram Folkative accounts there are Metaphor 3 data (2%); Litotes 3 data (2%); Acronyms 21 data (16%); Abbreviations 61 data (47%); Clipping 11 data (9%); Synecdoche 4 data (3%); Idioms 17 data (13%); Borrowing 6 data (5%); Reduplication 2 data (2%); Omissions 1 data (1%). The researcher found 3 functions euphemism from Captions of Folkative Instagram account namely, Informs 77 data (60%); Evaluates 30 data (23%); Modalizes 22 data (17%). Based on the data found, the most widely used type of euphemism by Instagram Folkative accounts is Abbreviations with 61 data and the function of euphemism used is Informs with 77 data.